2018
DOI: 10.1002/app.47014
|View full text |Cite
|
Sign up to set email alerts
|

Stress–thermal oxidative aging behavior of hydrogenated nitrile rubber seals

Abstract: The long-term thermal oxidative aging behavior of uncompressed and compressed hydrogenated nitrile rubber seals was studied in terms of the weight loss, chemical structure, crosslinking density, compression set, fracture morphology, and mechanical properties. It was found that weight loss of the uncompressed seals was more than that of the compressed seals due to restricted mobility of additives and molecular chains under compression. The ATR-FTIR results showed that hydroxyl groups and carbonyl groups both we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…e crosslinking densities of vulcanizates were determined by the Flory-Rehner equation shown in equation (1). To achieve their swollen equilibrium, weighed samples were, respectively, immersed in toluene at room temperature for 72 hours.…”
Section: Tests and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…e crosslinking densities of vulcanizates were determined by the Flory-Rehner equation shown in equation (1). To achieve their swollen equilibrium, weighed samples were, respectively, immersed in toluene at room temperature for 72 hours.…”
Section: Tests and Analysismentioning
confidence: 99%
“…Rubber materials are widely used in industrial fields because of their high elasticity and excellent damping properties [1,2]. However, fatigue failures that are common in rubber components remain a key issue.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for vibrational dampers and shock absorbers, the performance of fatigue resistance under compressive conditions is of great importance. Nowadays, few research studies focus on the compressive fatigue mechanism of styrene-butadiene rubber (SBR), which is a kind of non-crystallizable rubber and contains excellent damping behavior over a wide range of temperatures and frequencies [ 1 , 2 , 3 ]. As it is very different from natural rubber (NR), the fatigue mechanism of SBR is not dependent on the strain crystallization, so that it is very suitable for studying the fatigue mechanism [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different media had been introduced to several tests in order to find the aging behaviors of NBR. The epoxidation degradation activation energy value of a NBR was measured to be 82 kJ/mol, and it had been proved that the aging conditions (elevated temperature and compressive stress) did not significantly affect the thermal stability of the rubber seals 8–10 . Results indicated that the friction coefficient increased but the wear volume decreased with aging time was conducted by an experimental study 11,12 of a NBR steel pair, and the influence of shedding light was also considered.…”
Section: Introductionmentioning
confidence: 99%